about -85.66666666
Chat with our AI personalities
The given expression is x + 6 = 2x + 5. Subtract both sides by x to get: x - x + 6 = 2x - x + 5 6 = x + 5 Subtract both sides by 5 to get: 6 - 5 = x + 5 - 5 x = 1
If 5 X 6 = 30 OR 6+6+6+6+6=30 Because 5 stands for the amount of sixes you add together so if 5 X 6 = 30 then 6 X 6 would just add six to the 5 X 6 6 X 6 = 36 5 X 6 = 30 36 - 30 = 6 Because all you did was add six.
2 x (-6) x 5 = -60
1/6 + 1/5 the common denominator is 30 = (1 x 5)/(6 x 5) + (1 x 6)/(5 x 6) = 5/30 + 6/30 = (5 + 6)/30 = 11/30
32